The block therapy in the treatment of cancer pain - Grünwald, Izso; Rosasco, Carlos L (Cirugía del Uruguay, 2020)
Pain caused by malignancies diseases remains a concern and issue study and research by doctors, and is a cause of suffering for many patients ...